The Influence of Muslim-Friendly Tourism on Foreign Tourist Visits in ASEAN - Ahmad Yunadi; Defia Ifsantin Maula; Tutut Nur Indiani Al Adhawiyah. S; Victoria Nikmatul Ula (El-Qish: Journal of Islamic Economics, 2024)
Indicator Muslim Friendly Tourism (MFT) partially has a significant effect on the number of foreign tourists in ASEAN countries. The MFT indicator is selected from the variables Global Muslim Travel Index (GMTI) published by Mastercard-CrescentRating every year. Of the six MFT indicators, three have a significant effect, namely the Muslim Variable-Friendly Airports (X3) with a probability value of 0.002 or 0.2%, Heritage Experiences and Attractions (X4) probability value of 0.025 or 2.5%, and availability of Prayer Places and Mosques, Availability of Halal Dining Options (X6) with a probability value of 0.000. Of the three selected GMTI variables, the probability value is smaller than 5%. The MFT indicator simultaneously also influences foreign tourist visits. The test results together obtained a probability value smaller than 0.05, namely 0.0000. Meanwhile, the results of the coefficient of determination test for the equation obtained an adj R-squared value of 0.5425, which means that the 6 independent variables selected can influence the number of foreign tourists by 54.25% and the remainder is influenced by other factors outside the selected variables.